The Effect of Health Program in Primiparous Mother for Breast Feeding By family participation - Kingkloiklang, Sangdaun (Journal of Preventive Medicine Association of Thailand, 2020)
The aims of research to compare knowledge and family participation of breast feeding between primiparous mothers received health promotion program and primiparous mothers not received health promotion program. Sixty of primiparous mothers at 32-36+6 weeks in the antenatal care clinic of Chumphae Hospital between June 2019 and December 2019 were included and then randomized into two groups. A group of 30 primiparous mothers received health promotion program as Group A (study group). A group of 30 primiparous mothers not received health promotion program as Group B (control group) then sampling by block of four into two groups. This study was a randomized controlled trial. Study group received health promotion program 2 time before delivery at 32-36+6 weeks and 37-42 weeks. The data were collected by questionnaires and record form then analyzed b mean, percentage, SD and paired t-test. The results after delivery study group had 21 samples control groups had 25 samples showed no statistically significant difference in characteristic data but statistically significant difference in knowledge and family participation of breast feeding between both groups. Knowledge of breast feeding pretest of study group mean 6.38 control group 5.76 (p=0.191) and posttest of study group mean 9.76 control group 7.28 (p=<0.001). Family participation of breast feeding of study group 16 (76.19%), mother was the most participation and most satisfactory 14 (66.67%), control group 6 (24.00%) (p=0.001) mother was the most participation and most satisfactory 7 (28.00%) (p=0.016). Study group most used 6 methods more than control group used 2 method for stimulated breast feeding. The study group and control group found mean body weight of newborn 3,075.47g (SD375.65) and 3015.56g (SD375.63) mean body weight of 48 hours newborn 2,875.95g (SD353.36) and 2,812.20g (SD367.3) mean of MB at 48 hours newborn 9.28 (SD1.56) and 9.17 (SD1.80) no statistically significant difference but statistically significant difference in milk ejection level 3 study group found 11 (52.38%) control group found 6 (24.00%) (p=0.047)